Short- and long-term outcomes of 486 consecutive laparoscopic splenectomy in a single institution. Issue 13 (2nd April 2021) - Fu, Xiaowei; Yang, Zhengjiang; Tu, Shuju; Xin, Wanpeng; Chen, Haiming; Li, Xueming; Li, Yong; Xiao, Weidong
Abstract : Abstract: Since its introduction in 1991, laparoscopic splenectomy (LS) has become the gold standard in elective spleen surgery in many centres. However, there still lack the report of long-term outcomes of LS with the large-scale cases. The aim of the present study was to analyze the short- and long-term outcomes of LS in a single institution over 16 years, and to compare the perioperative outcomes of totally laparoscopic splenectomy (TLS) and hand-assisted laparoscopic splenectomy (HALS) for splenomegaly. Between November 2002 and December 2018, 486 consecutive patients undergoing elective LS were enrolled in this study, including 222 TLS and 264 HALS. The intraoperative, postoperative, and follow-up data were retrospectively analyzed. The 5 most common indications were hypersplenism (71.0%), immune thrombocytopenia (14.8%), splenic benign tumor (4.5%), splenic cyst (2.9%), and splenic malignant tumor (2.9%). The mean operative time, intraoperative blood loss, and length of stay were 149.4 ± 63.3 minutes, 230.1 ± 225.1 mL, and 6.7 ± 3.2 days, respectively. The morbidity, mortality, reoperation, and conversion rate were 23.0%, 0, 0.4%, and 1.9%, respectively. Portal vein system thrombosis (PVST) was the most frequent complication with an incidence of 19.8%. The incidence of PVST in HALS was higher than that in TLS (23.9% vs 14.9%, P = .013). Compared with TLS, HALS had a shorter operative time ( P = .000), lower intraoperative blood loss ( P = .000), comparable conversion rate ( P = .271), and morbidity ( P = .922) for splenomegaly > 17.0 cm. During the follow-up period, the overall respond rate for immune thrombocytopenia was 77.8%, and the esophagogastric variceal bleeding rate was 6.9% in 320 patients with hypersplenism secondary to hepatic cirrhosis. LS is a safe, feasible, and effective procedure with satisfactory short- and long-term outcomes. HALS is a reasonable technique in patients with massive spleens.